2018
DOI: 10.1108/intr-06-2017-0240
|View full text |Cite
|
Sign up to set email alerts
|

Empathy or perceived credibility? An empirical study on individual donation behavior in charitable crowdfunding

Abstract: Purpose Researchers have called for the synthesis of divergent perspectives and the development of a theoretical model that examines individuals’ donation behavior in charitable crowdfunding. To fill this research gap, the purpose of this paper is to synthesize the literature pertaining to the determinants of donation behavior in charitable crowdfunding. Then, drawing on the stimulus-organism-response framework, the authors develop and test a model that explains individuals’ intention to donate to charitable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
222
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(256 citation statements)
references
References 101 publications
15
222
0
8
Order By: Relevance
“…We concluded that a single individual VIF score was below three, whereas, the tolerance values ranged from 0.6 to 0.9. According to Hair et al [74] and Liu et al [75], the VIF values were far below the suggested value of 10. The VIF and tolerance values of this study were also within the criteria (VIF < 5 and Tolerance > 0.2) indicating that the multicollinearity of the measures was not likely to be a concern.…”
Section: Multicollinearity Analysismentioning
confidence: 89%
“…We concluded that a single individual VIF score was below three, whereas, the tolerance values ranged from 0.6 to 0.9. According to Hair et al [74] and Liu et al [75], the VIF values were far below the suggested value of 10. The VIF and tolerance values of this study were also within the criteria (VIF < 5 and Tolerance > 0.2) indicating that the multicollinearity of the measures was not likely to be a concern.…”
Section: Multicollinearity Analysismentioning
confidence: 89%
“…The few existing empirical studies on donation-based crowdfunding predict user intention to donate rather than the actual donation behavior (L. Liu, 2018;T. Wang, Li, Kang, & Zheng, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan carian, hanya lapan (8) artikel berbentuk kuantitatif yang memberi fokus kepada faktor-faktor orang ramai menyumbang dalam pendanaan awam bertujuan kebajikan. Keputusan carian menunjukkan, pendanaan awam bertujuan kebajikan mula dibincangkan secara bermula tahun 2018 dari pelbagai jurnal penerbitan oleh penyelidik berikut; Majumdar dan Bose 2018 Bagi populasi negara, didapati negara China dan Amerika Syarikat mendominasi perbincangan berkaitan dengan gelagat penyumbang dana melalui platform pendanaan awam, iaitu artikel yang ditulis oleh Li et al (2017), Liu et al (2018), Zemack-Rugar dan Klucarova-Travani (2018) serta Cho et al (2019) Penulis mendapati pelbagai faktor yang mendorong orang ramai melakukan sumbangan kepada pendanaan awam bertujuan kebajikan. Faktor-faktor tersebut penulis rangkumkan dalam Jadual 4.…”
Section: Analisis Deskriptifunclassified
“…Platform mudah digunakan (perceived easy to use) perkhidmatan kewangan ini sebenarnya menambahkan lagi jaringan sosial dan keperluan kognitif manusia, berbanding keperluan kewangan kerana setiap pihak akan memastikan kempen disampaikan dengan positif melalui cara yang tersendiri. Platform yang berkualiti ini juga turut dibantu dengan kemudahan transaksi sistem pembayaran atas talian menurut tiga artikel yang tulis oleh Li et al (2017), Liu et al (2018) dan Mohd Thas Thaker et al 2018bagi memudahkan transaksi kewangan di antara crowdfunder dan penyumbang dana (Gerber & Hui 2013). Kemudahan transaksi ini berkait rapat dengan elemen masa dan kemudahan untuk orang ramai menggunakannya di tempat atau negara yang berbeza.…”
Section: Sasaki (2019)unclassified
See 1 more Smart Citation